Heat stroke of a massive body with an internal spherical crack - E. M. Kartashov; I. A. Nagaeva (Тонкие химические технологии, 2014)
The role of inertial effects in the problem of heat stroke with a massive body having an internal spherical crack as an example was studied. An interrelationship for the calculation of the maximum dynamic stress, which is of great practical importance, is suggested.